BENTUK PERTUNJUKAN TARI NYI KABARIAH DALAM ACARA ARAK TUMPENG PANCA THUK - Natasya Putri Ken Rosa; Anggono Kusumo Wibowo; Samsuri (Institut Seni Indonesia Surakarta, 2026)
This study aims to describe and analyze the form of the Nyi Kabariah Dance performance. The Kabariah Dance is a dance work created based on the history of the Kabariah puppet from Pakel Village, Jombang, and is performed in a traditional ceremonial procession called Arak Tumpeng Panca Thuk. This dance work was created by two choreographers, Merliani and Natasya Putri, in 2025. The dance is a group choreography inspired by the history of the Kabariah Puppet, which in the past served as a medium for conveying messages of soldiers victory. Thrpugh a qialitative approach with an analysis of performance elements, the results of the study indicate that the Nyi Kabariah Dance integrates visual aspects and philosophical values harmoniously. The structure of the dance presentation is divided into two acts that depict a character transition, beginning with the introduction of the Kabariah puppet’s form and culminating in expressions of grace and patriotism. The main appeal of thi dance lies in the stylized movements that show sharp and jerky dynamics, yet are still performed with full elegance. Supported by dynamic Javanese gamelan music and costume designs in shades of yellow, orange, maroon, and brown, the Nyi Kabariah Dance successfully represents the symbolism of joy and local strength. Overall, this form of performance is not merely a matter of stage aesthetics, but an effort to preserve history through the transformation of movement art that is communicative for modern society.